Design Developer Competition in Stockholm: A case study on innovation, architecture, and affordable housing - Rönn, Magnus (Enquiry The ARCC Journal for Architectural Research, 2019)
This case study examines a developer competition held in Stockholm in 2013-2014 organized by the municipal government. The objective was to develop good and affordable housing for young citizens. Fifteen design teams took part in the competition. The jury compared two different proposals in the final evaluation: one with separate rooms linked to a collective space and one that consisted of small housing units. This sorting of design proposals in two main categories had a major impact on the judging in the competition. The jury declared the solution with small housing units as the winner, which reinforced the overall category as the appropriate direction for the design solution. There are three typical key players in the competition: the organizer, the jury, and the design teams. The organizer was responsible for the objective and terms presented in the brief. The jury was responsible to assign a winner. Architects, builders, and developers responded to the task by organizing design-teams and producing architectural design solutions. They had to understand affordability as both cost (rent level) and architectural design (area-effective apartments). The competition in Stockholm was investigated in a case study. Research data was collected from archives and through questionnaires answered by jury members and design teams. Methods used for analyzing documents and design solutions were close reading and architectural criticism. Twenty-two architectural students studied the competition in a course. In this case study, I compare how the professional jury evaluated the proposals to jury reports from the students focusing on innovative solutions. The professional jury and the student juries used the same criteria for judging but appointed different winners. The students preferred the solution with collective living. One explanation for this difference can be found in the structure of the evaluation process. The results of the study can be summarized in ten conclusions that deal with sorting and ranking of design proposals, criteria for judging, marketing of the competition, uncertainty and knowledge, motives for competing, innovation, and the competition as a tool for the political ambition of the public organizers. The result produced new knowledge. There are few studies focusing on developer competition as the production of design proposals and architectural quality.